2022
DOI: 10.1155/2022/6216072
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Clinicopathological Factors Associated with Radiation-Induced Cystitis in Patients with Cervical Cancer

Abstract: Objective. To analyze the clinicopathological characteristics associated with radiation-induced cystitis (RIC) in patients with cervical cancer treated with chemoradiotherapy (CRT) alone or postoperational (post-op) CRT. Methods. 107 patients with cervical cancer were retrospectively recruited into the study. The surgical status, FIGO staging, total and fractionated doses of radiotherapy (RT), and multiparameters including the dose, volume irradiated to the total bladder, and bladder wall were evaluated for RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Radiation cystitis is one of the most common complications of radiation therapy and significantly affects patients' quality 25 mg Excipients: Starch, magnesium stearate, talc, PVP K30, microcrystalline cellulose, HPMC of life and can lead to life-threatening situations (10)(11)(12). The combination of surgery and post-surgical radiochemotherapy may increase the incidence and severity of radiation-induced cystitis compared to radiotherapy alone, suggesting that bladder dysfunction due to the surgical procedure may increase the frequency and severity of radiation cystitis as it was seen in the reported patient (13). Surgical procedures may partially destroy the autonomic bladder nerve, causing the decrease of the bladder wall's elastic muscle fibers, leading to neurogenic bladder dysfunction resulting in frequent urination, urgency, and urinary incontinence (14).…”
Section: Discussionmentioning
confidence: 76%
“…Radiation cystitis is one of the most common complications of radiation therapy and significantly affects patients' quality 25 mg Excipients: Starch, magnesium stearate, talc, PVP K30, microcrystalline cellulose, HPMC of life and can lead to life-threatening situations (10)(11)(12). The combination of surgery and post-surgical radiochemotherapy may increase the incidence and severity of radiation-induced cystitis compared to radiotherapy alone, suggesting that bladder dysfunction due to the surgical procedure may increase the frequency and severity of radiation cystitis as it was seen in the reported patient (13). Surgical procedures may partially destroy the autonomic bladder nerve, causing the decrease of the bladder wall's elastic muscle fibers, leading to neurogenic bladder dysfunction resulting in frequent urination, urgency, and urinary incontinence (14).…”
Section: Discussionmentioning
confidence: 76%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%